2007
DOI: 10.1086/522928
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-rich Mass Loss with a Pinch of Salt: NaCl in the Circumstellar Gas of IK Tauri and VY Canis Majoris

Abstract: The NaCl molecule has been observed in the circumstellar envelopes of VY Canis Majoris (VY CMa) and IK Tauri (IK Tau)-the first identifications of a metal refractory in oxygen-rich shells of evolved stars. Five rotational transitions of NaCl at 1 and 2 mm were detected toward VY CMa and three 1 mm lines were observed toward IK Tau, using the telescopes of the Arizona Radio Observatory. In both objects, the line widths of the NaCl profiles were extremely narrow relative to those of other molecules, indicating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
51
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 22 publications
8
51
0
Order By: Relevance
“…This is in accord with thermochemical equilibrium predictions, not taking phase changes into account, predicting that the gaseous NaCl abundance peaks around 500 to 1200 K at densities n ∼ 10 11 cm −3 (see Fig. 3 in Milam et al 2007), with NaCl being the main sodium carrier in oxygen-rich environments 3 . For temperatures above 1500 K, the fractional abundance of gaseous NaCl is below 10 −12 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This is in accord with thermochemical equilibrium predictions, not taking phase changes into account, predicting that the gaseous NaCl abundance peaks around 500 to 1200 K at densities n ∼ 10 11 cm −3 (see Fig. 3 in Milam et al 2007), with NaCl being the main sodium carrier in oxygen-rich environments 3 . For temperatures above 1500 K, the fractional abundance of gaseous NaCl is below 10 −12 .…”
Section: Discussionsupporting
confidence: 88%
“…The 22 GHz and 321 GHz H 2 O maser features at the greatest angular separations lie approximately east and west or to the southwest. Milam et al (2007) observed several rotational lines in the ground vibrational state of NaCl using single-dish telescopes with beam sizes between 29 -44 . The NaCl emission was spatially unresolved and modelling the observed spectra resulted in an abundance relative to H 2 of 5 × 10 −9 with a source size of 0.5 .…”
Section: Morphological Comparison To Other Tracers Of the Envelopementioning
confidence: 99%
“…The main Gaussianlike component of the TiO emission, however, is very likely formed in the inner outflow because it is centrally peaked and much narrower than 2V ∞ . Similar narrow molecular emission lines in VY CMa have been attributed to the accelerating wind (e.g., Milam et al 2007). Following Tenenbaum & Ziurys (2009) and Kamiński et al (2013), to better localize the TiO emission region we use the semi-empirical windacceleration model in VY CMa constrained from multi-epoch observations of H 2 O masers (Richards et al 1998).…”
Section: Localization and Abundances Of The Tio And Tio 2 Gasmentioning
confidence: 94%
“…The angular diameter is estimated around 20 mas (Decin et al 2010a). Currently, a dozen different molecules and some of their isotopologues have been discovered in IK Tau, including CO, HCN, SiO, SiS, SO, SO 2 , NaCl, NS, NO, HCO + , H 2 CO, PO, PN, and H 2 S (Milam et al 2007;Kim et al 2010;Decin et al 2010a,b;De Beck et al 2013Velilla Prieto et al 2017). Some molecules including SiO and SiS are depleted in the circumstellar envelope, possibly owing to condensation onto dust grains.…”
Section: Target Selectionmentioning
confidence: 99%